Lipid storage myopathy due to late-onset multiple Acyl-CoA dehydrogenase deficiency with novel mutations in ETFDH: A case report - Tian, Huihong; Zhong, Yi; Liu, Zhihua; Wei, Liping; Yuan, Yanbo; Zhang, Yuhu; Wang, Limin (Frontiers in Neurology, 2022)
Background: Lipid storage myopathy (LSM) is an autosomal recessive inherited lipid and amino metabolic disorder with great clinical heterogeneity. Variations in the electron transfer flavoprotein dehydrogenase (ETFDH) gene cause multiple acyl-CoA dehydrogenase deficiency (MADD), with a manifestation of LSM. Muscle biopsy helps clarify the diagnosis of LSM and Next-generation sequencing (NGS) can be useful in identifying genomic mutation sites. And the diagnosis of MADD contributes to targeted therapy. Case presentation: We report a teenager who appeared muscle weakness and exercises intolerance at the onset. He was treated as the suspect of polymyositis without efficacy before referral to our hospital. However, the biopsy demonstrated lipid accumulation in muscle fibers, suggesting LSM. Next-generation sequencing of the proband and his parents revealed heterozygous variations, c.365G>A (p.G122D) inherited from the father, c.176-194_176-193del, and c.832-316C>T inherited from the mother in the ETFDH gene, Tandem Mass Spectrometry identified these mutations were pathogenic. However, his parents and his younger sister who detected mutation of c.365G>A presented no clinical symptoms. This indicates that the combination of three compound heterozygous mutations ETFDH is significant. MADD was diagnosed, and dramatic clinical recovery and biochemical improvement presented as riboflavin was used on the patient in a week, which further confirmed the diagnosis of MADD. Conclusions: Our observations extend the spectrum of ETFDH variants in Chinese papulations and reinforce the role of NGS in the diagnosis of MADD. Early diagnosis and appropriate treatment of LSM lead to great clinical efficacy and avoid some lethal complications.